Decalcifying efficacy of different irrigating solutions: effect of cetrimide addition - POGGIO Claudio; DAGNA Alberto; COLOMBO Marco; SCRIBANTE Andrea; CHIESA Marco (Sociedade Brasileira de Pesquisa Odontológica, 2014)
The objective of the present study was to evaluate and compare the influence of cetrimide on decalcifying capability of different irrigating solutions. Fifteen maxillary central incisor teeth has been collected. The canals were prepared in order to obtain four samples from each root. The specimens were randomly divided into 6 experimental groups (n=10) according to tested irrigating agents. Irrigating agents consisted in different composition of EDTA and citric acid solutions, addicted or not with cetrimide. Each specimen was submitted to three successive 5-min immersions in each solution. After exposures, the concentration of Ca2+ extracted was measured by inductively coupled plasma-atomic emission spectrometry (ICP-AES). Data were analysed by means of Kruskal Wallis and Mann Whitney tests. Significance was predetermined at p < 0.05. For all irrigants, the amounts of Ca2+ extracted from root canal dentin samples at 10 minutes were not significantly different from values reported after 15 minutes respectively. Therefore, for all irrigants tested, 10 minutes of application are sufficient to obtain maximum Ca2+ release. Moreover citric acid based agents observed a higher release of Ca2+. The addition of cetrimide did not affect the decalcifying capability of the EDTA and citric acid solutions.